My world of color - Brown, Margaret Wise, 1910-1952.; Krupinski, Loretta (New York : Hyperion Books For Children, 2002)
Rhyming verses describe things that are red, orange, yellow, green, blue, purple, brown, black, gray, white, and pink.
Keywords: Color -- Fiction; Stories in rhyme